Motivation In Good Dealings: An Analysis Of Surah Ad-Dhuha From The Psychological And Rhetorical Perspectives - Wan Azura Wan Ahmad; Hishomudin Ahmad; Yuslina Mohamed; Fazullah, MZAA; Samah, R; Ibrahim, M (Univ Sultan Zainal Abidin, 2024)
Indexed by WOS